2016
DOI: 10.1161/atvbaha.115.307412
|View full text |Cite
|
Sign up to set email alerts
|

Oncological miR-182-3p, a Novel Smooth Muscle Cell Phenotype Modulator, Evidences From Model Rats and Patients

Abstract: Objective— Vascular smooth muscle cell (VSMC) phenotype change is a hallmark of vascular remodeling, which contributes to atherosclerotic diseases and can be regulated via microRNA-dependent mechanisms. We recently identified that asymmetrical dimethylarginine positively correlates to vascular remodeling–based diseases. We hypothesized that asymmetrical dimethylarginine induces smooth muscle cell (SMC) phenotypic change via a microRNA-dependent mechanism. Approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In recent years, miR-182 can regulate a series of physiological processes such as growth, development, and cell differentiation of biological organisms by regulating the expressions of different target genes. It also plays an oncogene in the process of malignant tumors [23,24]. The results of this study showed that the expressions of miR-182 in LSCC tissues and cells was significantly lower than that of normal adjacent normal tissues and normal cells (P<0.05).…”
Section: Discussionmentioning
confidence: 64%
“…In recent years, miR-182 can regulate a series of physiological processes such as growth, development, and cell differentiation of biological organisms by regulating the expressions of different target genes. It also plays an oncogene in the process of malignant tumors [23,24]. The results of this study showed that the expressions of miR-182 in LSCC tissues and cells was significantly lower than that of normal adjacent normal tissues and normal cells (P<0.05).…”
Section: Discussionmentioning
confidence: 64%
“…The etiology of these alterations in VSMC phenotype is still unclear. Recent reports have demonstrated that miRNAs participate in the regulation of the phenotype of VSMCs [2729]. Selective expression of miR-145 occurs in murine VSMCs, which is remarkably inhibited during the alteration in phenotype triggered by PDGF-BB in vitro as well as in balloon-damaged murine arteria carotis.…”
Section: Discussionmentioning
confidence: 99%
“…Of great interest to us is the growing evidence that supports a role for a novel class of gene regulators, microRNAs (miRs), in regulating VSMC differentiation from stem/progenitor cells and VSMC phenotype switching in response to vascular injury36. Despite the growing number of identified miRNAs that have been implicated in VSMC differentiation and phenotypic modulation in response to injury, such as miR-17, miR-15b/168, miR-219, 10, miR-34a11, 12, miR-13313, miR-143/145 cluster1420, miR-182-3p21, miR-21422, miR-221/22223, 24, miR-63825, and miR-66326, the epigenetic regulation of VSMC phenotype switching has yet to be fully understood.…”
Section: Introductionmentioning
confidence: 99%